Teaching migrant learners: the interplay between school culture and teacher multicultural self-efficacy - Mäe, Karolin; Ümarik, Meril (Frontiers in Education, 2025)
With increasing global migration, multicultural classrooms have become an everyday reality for educators across the Globe. Yet many teachers report feeling unprepared to meet the needs of culturally diverse learners. Teacher multicultural self-efficacy is recognized as a key belief in effective teaching. This study examines the interplay between school culture and teachers’ multicultural self-efficacy from a qualitative perspective. Drawing on in-depth interviews with 20 basic school teachers in Estonia, a country with increased migration, where diversity is a relatively novel aspect in classrooms. Research identifies four distinct teacher profiles that vary in their levels of multicultural self-efficacy, diversity experience, teaching strategies, perceptions of collective efficacy, and experiences of school culture. Findings indicate that a collaborative school culture, characterized by cooperation between teachers and support staff, as well as the whole school’s approach to diversity, supports teachers’ multicultural self-efficacy. Study advances theoretical understandings of how systemic, cultural, and interpersonal dynamics intersect to either support or constrain effective teaching in multicultural classrooms. The article contributes practical insights for cultivating supportive school cultures that enhance teachers’ capacity to meet the needs of diverse learners.